2021
DOI: 10.4102/jamba.v13i1.974
|View full text |Cite
|
Sign up to set email alerts
|

Climate change adaptation strategies and their predictors amongst rural farmers in Ambassel district, Northern Ethiopia

Abstract: The present study was conducted in Ambassel district of Northern Ethiopia to understand adaptation strategies employed by rural farmers to the adverse effects of climate change and variability and factors that determine their adaptation decisions. The study was based on multistage sampling techniques to select the study villages and sampled households (HHs). Data were collected through HH survey, focus group discussions and key informant interviews. The collected data were analysed by using descriptive statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 34 publications
6
15
1
Order By: Relevance
“…Research by Amare (2018) conducted in Ethiopia reveals that literate household heads are more likely than illiterate household heads to be aware of climate change and variability. According to Destaw and Fenta (2021), this indicates that literate smallholder farmers are more adept at using contemporary technology to manage climate change and fluctuation than their illiterate counterparts. Education aids smallholder farmers in better understanding and employing adaptation strategies for climate change and unpredictability, claim Addisu et al (2016).…”
Section: Educational Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Research by Amare (2018) conducted in Ethiopia reveals that literate household heads are more likely than illiterate household heads to be aware of climate change and variability. According to Destaw and Fenta (2021), this indicates that literate smallholder farmers are more adept at using contemporary technology to manage climate change and fluctuation than their illiterate counterparts. Education aids smallholder farmers in better understanding and employing adaptation strategies for climate change and unpredictability, claim Addisu et al (2016).…”
Section: Educational Statusmentioning
confidence: 99%
“…Farmers can use a variety of adaptation strategies by being informed about the present climatic conditions via weather information. Destaw and Fenta (2021) assert that access to meteorological information improves rural families' comprehension of the environment, its unpredictable nature, and the significance of adaptation measures. The marginal effect finding indicates that access to meteorological information will increase climate change adaptation measures by 4.7%.…”
Section: Access To Weather Informationmentioning
confidence: 99%
“…Even though the country has scattered climate change policies, strategies and programmes in place, still climate change is acute problem in the country. Moreover, scholars argue that even though the country has started adaptation interventions against adverse effects of climate change, endeavours are still at a relatively early phase: it is practically more acceptable to state that these implementation measures are fragmented and limited (Destaw and Fenta, 2021). Hence, the purpose of this article is to critically compare and analyse Ethiopia's national climate change mitigation and adaptation regulatory frameworks to know whether the country has paid attention to or adhered to the United Nations Framework Convention on Climate Change (UNFCCC) principles or not.…”
Section: Appraisal Of Climate Change Mitigationmentioning
confidence: 99%
“…change [35]. The adaptation methods used in the agriculture sector include the use of improved crop varieties, application of inorganic fertilizers, conservation agriculture, soil and water Management (in situ water harvesting measures, soil and water conservation measures, and supplementary irrigation), agroforestry, adjusted sowing dates, and application of organic fertilizers (see Table 1) [18,19,29,33,36,37]. From these practices, the use of improved crop varieties, conservation agriculture, soil and water Management (in situ water harvesting measures, soil and water conservation measures, and supplementary irrigation), agroforestry, adjusted sowing dates, and application of organic fertilizers are nature-based climate change adaptation measures.…”
Section: Parkland Agroforestry System and Practicementioning
confidence: 99%
“…For example, changing sowing date (30.8 %) followed by fertilizer application(21.4%) and crop diversification (19%) used in lowland area, while terracing (57.5 %) followed by changing sowing date (11%), crop diversification (7.8 %) and income diversification (7.6 %) used in high land areas Northern Ethiopia [36] Similarly, [57] indicated that higher soil moisture content at outer tree canopy cover area of Albizia saman (9 m distance) than in the open area (non-canopy cover) in the maize fields in the case of Annamalai Nagar, Tamil Nadu, India. Consequently, significantly higher LAI, biological yield and grain yield of maize were noticed under the canopy of A. saman from 3 m to up to 9 m distance apart the trunk of A. saman.…”
Section: Parkland Agroforestry System and Practicementioning
confidence: 99%